Reference trajectory-based coverage analysis method in three-dimensional space for multi-radio integrated navigation systems. (1st October 2020) - Son, Jae Hoon; Oh, Sang Heon; Hwang, Dong-Hwan
ABSTRACT: GPS can be integrated with other radio navigation systems when GPS signals are not available due to navigation warfare. Before deploying navigation signal sources, the coverage analysis can be performed in order to check a required navigation performance is satisfied in 2-dimensional space. Usually, the coverage analysis is performed for the area in which a vehicle is operated. When an air vehicle is operated and the method in 2-dimensional is directly extended, the computational load can be excessively heavy. In this paper, a reference trajectory-based coverage analysis method for multi-radio integrated navigation systems is proposed using CRLB in order to alleviate computational burden in 3-dimensional space. The performance of the proposed method is evaluated for 2 trajectories and 6 arrangements of navigation signal sources. The results show that the proposed method can be used in the coverage analysis in 3-dimensional space.